Dosing regimen of oxytocin antagonist for promoting embryo implantation and preventing abortion - LOUMAYE ERNEST; GOTTELAND JEAN-PIERRE (2023)
The present invention provides compositions and methods for using oxytocin antagonists, such as substituted pyrrolidine-3-ketoxime derivatives, in the treatment of subjects undergoing embryo transplantation therapy. The compositions and methods of the invention may be used to administrate oxytocin antagonists to a subject, including (3Z, 5S)-5-(hydroxymethyl)-1-[(2 '-methyl-1, 1'-biphenyl-4-yl) carbonyl] pyrrolidin-3-one O-methyl oxime, etc. The present invention relates to a method for improving endometrial receptivity and reducing the likelihood of embryo implantation failure and abortion after, for example, in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) embryo transplantation procedures. 本发明提供了在治疗经历胚胎移植疗法的受试者中使用催产素拮抗剂例如取代的吡咯烷-3-酮肟衍生物等化合物的组合物和方法。本发明的组合物和方法可用于给受试者施用催产素拮抗剂，包括(3Z,5S)-5-(羟甲基)-1-[(2'-甲基-1,1'-联苯-4-基)羰基]吡咯烷-3-酮O-甲基肟等等，以在例如体外受精(IVF)和胞浆内精子注射(ICSI)胚胎移植程序之后改善子宫内膜容受性并降低胚胎植入失败和流产的可能性。